Magnetic Resonance Imaging Findings After Superior Capsule Reconstruction - Dale Nicholas Reed, M.D; James Tyler Frix, M.B.A; James Mitchell Frix, M.D (Elsevier, 2021)
Purpose: To evaluate graft properties on magnetic resonance imaging (MRI) after superior capsular reconstruction (SCR) to help improve our understanding of postoperative imaging. Methods: We identified consecutive patients who underwent SCR by a single surgeon and who had postoperative MRIs available. MRIs were analyzed to look for common postoperative findings on imaging. Results: Ten consecutive patients with an average age of 58 years who underwent SCR by a single surgeon had postoperative MRIs on average 404 days from surgery. Eight patients had completely intact grafts on follow-up MRI. All intact grafts were similar with homogenous appearance on all coronal images. All patients displayed some trace fluid with mild heterogenous signal at the level of the glenoid, which could represent failure of the graft to completely incorporate at the level of the glenoid or could be normal in the postoperative setting since all eight intact grafts displayed this finding. None of the patients with intact grafts had bony edema noted on either the glenoid or humeral side. Four of 8 patients were noted to have trace bony edema at the level of the lateral acromion. One patient had complete disruption on the glenoid side. One patient had partially intact graft that revealed heterogenous appearance of graft. Conclusions: An intact graft displays a more homogenous signal on consecutive postoperative MRI coronal images than disrupted grafts or partially intact grafts. This suggests that intact grafts have better clinical outcomes than a partially disrupted or completely disrupted graft. However, the finding of heterogenous signal/fluid at the glenoid graft interface in all intact grafts could not be explained in this study. Level of Evidence: Level IV, therapeutic case series.